Ethics briefing - Norcliffe-Brown, Dominic (Journal of medical ethics, 2021)
As the COVID-19 vaccine roll out continues apace, in the higher-income countries at least, concerns remain about the level of vaccine coverage in some health and social care settings. Although most countries have seen a relatively high uptake of vaccination against COVID-19 among staff, there continue to be some pockets of hesitancy. The risk of outbreaks in settings with potentially very vulnerable patients has led some governments across Europe to consider, or to introduce, measures compelling healthcare staff to be vaccinated.The justifiability of mandating the vaccination of healthcare professionals is a longstanding question but it has come to the fore in recent months following a resurgence of cases of COVID-19 and the prevalence of the more transmissible Delta variant. In deciding whether the introduction of a mandate is appropriate, states have to balance a range of ethical and practical considerations. A voluntary approach, backed up with education, respects healthcare workers’ autonomy to make private healthcare decisions, which is valued highly in liberal democracies. However, healthcare professionals also have an obligation to ensure that they do not present a risk of harm to their patients. Similarly, healthcare providers have a responsibility to take appropriate steps to minimise the risk of infection. Alongside balancing these rights and responsibilities, governments must also consider the potential consequences and risks of enforcing vaccine uptake. For example, there are concerns that a coercive approach could deepen mistrust and resentment among people who are genuinely fearful or hesitant. Moreover, a large number of refusals and the subsequent imposition of sanctions, such as suspension or redeployment, could affect the ability of providers to staff necessary services.In the UK, Wales, Northern Ireland and Scotland have all ruled out the introduction of compulsory vaccination. However, in July, the English Parliament voted through …